Influence of the Sulfur Content Catalyst on the Packing Density of Carbon Nanotube Forests - Moon, Sook Young; Kang, In Ji; Kim, Seung Min; Kim, Woo Sik (MDPI, 2019)
For the fabrication of high-performance carbon nanotube (CNT) composites with practical applicability, the development of new methods for the controlled growth of high-aspect-ratio CNTs still constitutes a challenge. With the aim of gaining a deeper understanding of the catalytic CNT growth, in this study, the effect of the catalyst composition is investigated using different mixtures of Fe-2(SO4)(3) and FeCl2 as catalysts. The relationship between the catalyst chemical state and the growth behavior of CNT forests is demonstrated by evaluating the alignment, diameter, length, and areal density of the CNT forests. When the Fe-2(SO4)(3) content is increased, the area density, the I-G/I-D ratio, and the crystallite size of the CNTs increase. Additionally, the obtained CNT forests exhibit good spinnability with increasing the sulfur content.
Keywords: COSO4/SIO2 CATALYST; SELECTIVE SYNTHESIS; GROWTH; FABRICATION; YARNS